Impact of Agricultural Output on Economic Growth in Nigeria: Application of Numerical Prediction and Econometric Analysis - et. al., OluwatoyeseOluwapemi Oyetade, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The agricultural sector, as a whole, of any nation has been affirmed as one the solution to economic growth challenges. Thus, the agricultural sector can largely impact economic growth, though the process and extent to which it influences economic growth, is a topic that has drawn vast attention from researchers. Hence, this study considers an investigation of the long-run relationship, specifically between agricultural output and economic growth in Nigeria. In order to holistically interpret the relationship between the variables examined, a numerical approach known as the block method is adopted to a mathematical model developed for the variables using the logistic growth model, in order to predict the dataset for years 2020 to 2025. This implies that the study made used of annual data for the period of 1981 to 2025. The econometric analysis was conducted using the ARDL bound test approach to examine the connection between the nation’s agricultural output and economic growth. The findings indicate the existence of long-run relationship among variables, likewise short-run relationship. The pairwise granger causality test shows that there is one-way causality moving from agriculture to economic growth. This indicates that agricultural output leads to economic growth, but economic growth does not lead to agricultural output. The results approve the positive link between agricultural output and economic growth, which is helpful to improve the nation’s economic outlook. Hence, this study emphasized and suggested the need to support agricultural sector through economic policies and finances.